The Relevance Of Islamic Education In The Digital Era - Nurhidayati, Titin; Hosna, Rofiatul; Rofiq, M. Nafiur (Proceedings of Annual Conference for Muslim Scholars, 2025)
This study aims to analyse the relevance of Islamic education in the digital age in instilling tolerance values based on local wisdom in Generation Z as a preventive strategy against the spread of online extremist narratives in Jember Regency, Indonesia. Using a phenomenological qualitative approach, data was collected through in-depth interviews, participatory observation, and digital documentation involving Islamic Education teachers, Gen Z students, and Islamic boarding school leaders. Data analysis was conducted using the Miles and Huberman model through the stages of reduction, presentation, and conclusion drawing. The results of the study show that an effective strategy for fostering tolerance is to integrate local wisdom values such as tepo seliro, gotong royong, saling nguwongke and ngaji kebangsaan into digital learning based on the principle of rahmatan lil 'alamin. Islamic education has proven to be relevant as an ideological and cultural bulwark in strengthening Gen Z's digital religious literacy and fostering resilience against narratives of extremism. This study emphasises the importance of collaboration between educational institutions, Islamic boarding schools, and digital communities to build a contextual moderate Islamic ecosystem.